PREP TION OF EXTRUDER EXTRUDED FISH SNACK USING TWIN SCREW STO GEC CTERISTICS OF THE PRODUCT - Basu, S.; Sharma, Shiv Kumar (Journal of Indian Fisheries Association, 2015)
A value-added extruded fish product was prepared with corn flour (80%) and fish (sciaenid) powder (20%), using a twin-screw extruder. The effect of different parameters like moisture, temperature, fish powder concentration, speed of the extruder and die-diameter on expansion ratio and crisp texture were studied. The storage characteristics of the final product were studied using three different types of packaging under nitrogen flushing. The study revealed that aluminium foil is the best packaging material to keep the product acceptable for more than three months. Key words: Extruded fish product, twin-screw extruder, storage characteristics